Joy to the world : Christmas stories from around the globe - Pirotta, Saviour (HarperCollins Publishers, 1998)
Presents five folktales related to Christmas, including "The Brave Little Camel" (Syria), "Baby in the Bread" (Malta), "The Gourd of Plenty" (Ghana), "Flowers for Jesus" (Mexico), and "Babushka" (Russia).